2015
DOI: 10.1007/s00294-015-0511-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of bacillithiol in intracellular metal processing

Abstract: Glutathione (GSH) is an abundantly produced low-molecular-weight (LMW) thiol in many organisms. However, a number of Gram-positive bacteria do not produce GSH, but instead produce bacillithiol (BSH) as one of the major LMW thiols. Similar to GSH, studies have found that BSH has various roles in the cell, including protection against hydrogen peroxide, hypochlorite and disulfide stress. BSH also participates in the detoxification of thiol-reactive antibiotics and the electrophilic metabolite methylglyoxal. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Prominent among these were SufCD, which are required to synthesize iron-sulfur (Fe-S) cofactors (52). S. aureus strains unable to properly process Fe-S proteins into their mature forms display global shifts in carbon flux and metabolic defects (47,51,(53)(54)(55). Consistent with these studies, we found that a clpC mutant had deficient respiratory growth.…”
Section: Discussionsupporting
confidence: 77%
“…Prominent among these were SufCD, which are required to synthesize iron-sulfur (Fe-S) cofactors (52). S. aureus strains unable to properly process Fe-S proteins into their mature forms display global shifts in carbon flux and metabolic defects (47,51,(53)(54)(55). Consistent with these studies, we found that a clpC mutant had deficient respiratory growth.…”
Section: Discussionsupporting
confidence: 77%
“…We also determined that similar to what has been reported for Bacillus subtilis (44), T. thermophilus BSH mutants were more sensitive to Zn(II) than the WT strain (data not shown). This information suggests that BSH has a general role in metal ion tolerance and/or buffering (45). Thermus mer operons are not the only ones that contain thiol-related genes; some alphaproteobacterial mer operons include gor, a glutathione reductase gene.…”
Section: Discussionmentioning
confidence: 99%
“…SufA and Nfu function as Fe-S cluster carriers in S. aureus (7,18). Genetic evidence suggests that SufT and bacillithiol also have roles in the maturation of Fe-S proteins (18)(19)(20).…”
mentioning
confidence: 99%